DDX17 nucleocytoplasmic shuttling promotes acquired gefitinib resistance in non-small cell lung cancer cells via activation of β-catenin. (1st August 2017) - Li, Kai; Mo, Chunfen; Gong, Di; Chen, Yan; Huang, Zhao; Li, Yanyan; Zhang, Jie; Huang, Lugang; Li, Yuan; Fuller-Pace, Frances V.; Lin, Ping; Wei, Yuquan
Abstract: Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are effective for non-small cell lung cancer (NSCLC) patients with EGFR mutations, almost all these patients will eventually develop acquired resistance to EGFR-TKI. However, the molecular mechanisms responsible for gefitinib resistance remain still not fully understood. Here, we report that elevated DDX17 levels are observed in gefitinib-resistant NSCLC cells than gefitinib-sensitive cells. Upregulation of DDX17 enhances the gefitinib resistance, whereas DDX17-silenced cells partially restore gefitinib sensitivity. Mechanistically, we demonstrate that DDX17 disassociates the E-cadherin/β-catenin complex, resulting in β-catenin nuclear translocation and subsequently augmenting the transcription of β-catenin target genes. Moreover, we identify two nuclear localization signal (NLS) and four nuclear export signal (NES) sequences mediated DDX17 nucleocytoplasmic shuttling via an exportin/importin-dependent pathways. Interruption of dynamic nucleocytoplasmic shuttling of DDX17 impairs DDX17-mediating the activation of β-catenin and acquired resistance in NSCLC cells. In conclusion, our findings reveal a novel and important mechanism by which DDX17 contributes to acquired gefitinib resistance through exportin/importin-dependent cytoplasmic shuttling and followed by activation of β-catenin, and DDX17 inhibition may be a promising strategy to overcome acquired resistance of gefitinib in NSCLC patients. Highlights: High DDX17 levels facilitate the development of gefitinib resistance in NSCLC cells. DDX17 is an exprotin/importin-dependent nucleocytoplasmic shuttling protein. DDX17 consists of two NLSs and four NESs sequences. DDX17 promotes β-catenin nuclear translocation via disassociation from E-cadherin. Dynamic nucleocytoplasmic shuttling of DDX17 is essential for its function.